2013
DOI: 10.1080/24748668.2013.11868652
|View full text |Cite
|
Sign up to set email alerts
|

Time-motion analysis on Chinese male field hockey players

Abstract: The aim of the study was to evaluate the match work-rate of Chinese field hockey players by analyzing the distance covered at different intensities pooled by specific positions during different periods of matches. Thirty-eight players from twenty-four male field hockey matches at the 11 th Chinese National Games were filmed and analyzed. Results showed that players covered an average distance of 7334±877m; 91.7% of this distance was covered at low and medium intensity; total distance covered in the first half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
2
16
2
Order By: Relevance
“…On the other hand, ECW is composed of water in support and transport tissues which may not be related to muscle strength. Both goalkeepers and the defenders have lower metabolic energy cost both in gaming days and along training sessions than players of other positions (Liu et al, 2013). Although goalkeepers and the defenders in the present study found with greater absolute water volume (as described in Table III), however, they exhibited poorest content of relative body water spaces (including both ECW and ICW).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…On the other hand, ECW is composed of water in support and transport tissues which may not be related to muscle strength. Both goalkeepers and the defenders have lower metabolic energy cost both in gaming days and along training sessions than players of other positions (Liu et al, 2013). Although goalkeepers and the defenders in the present study found with greater absolute water volume (as described in Table III), however, they exhibited poorest content of relative body water spaces (including both ECW and ICW).…”
Section: Discussioncontrasting
confidence: 46%
“…Although goalkeepers and the defenders in the present study found with greater absolute water volume (as described in Table III), however, they exhibited poorest content of relative body water spaces (including both ECW and ICW). In case of both midfielders and forwards, greater level of hydration is due to the fact that they appear to engage in moderate to high intensity activity more frequently, and for longer durations (Liu et al, 2013). This fact was further justified by the result as significant correlation found between hydration level and aerobic capacity (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The influence of the playing period on the performance of the players has been studied in other sports, such as futsal [ 47 , 48 ], basketball [ 49 ], rugby 7 [ 50 , 51 ], hockey [ 52 , 53 ], and handball [ 54 ], with the aim of studying the effect of fatigue on the physical demands of players during competition. A differentiation of beach handball compared to other collaboration-opposition sports that use common space and simultaneous practice would be the regulatory conditioner with respect to the final score that is determined by the independence of the result of each set.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the total distance covered by New Zealand men’s squad outfield hockey players over a 70-min match averaged 8160 m, of which high-intensity running (> 19 km.h -1 ) represented 6.1% (479 ± 108 m) and involved ~34 sprints per player; average sprint duration and mean recovery duration were 3.3 s and 125 s [ranging from < 20 s (16% of the time) to > 60 s (55%)], respectively [ 16 ]. Besides inherent variability of game characteristics in field hockey between playing positions and playing styles, it is remarkable that sprinting activities for forward players decrease by ~12% between the first and the second half [ 17 ]. In addition to the considerable aerobic demands placed on top-level field hockey players [ 16 ], the ability to repeatedly perform “all-out” efforts with incomplete recoveries (repeated-sprint ability or RSA) is considered an important fitness component of this sport [ 18 ].…”
Section: Introductionmentioning
confidence: 99%